2011
DOI: 10.1002/pssr.201105430
|View full text |Cite
|
Sign up to set email alerts
|

Binding energy of singlet excitons and charge transfer complexes in MDMO‐PPV:PCBM solar cells

Abstract: In recent years, joint efforts of a vast and expanding research community have led to a steady improvement of organic solar cell (OSC) power conversion efficiencies. However, even OSC record efficiencies of currently 8.3% [1] are still trailing behind the ones of their inorganic counterparts -a fact which can be attributed to the relatively low dielectric constants r ( 3 4) ε ªof the employed organic semiconductors. The resulting weak screening causes the primary photoexcitations, i.e. the singlet excitons S 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 19 publications
5
42
0
Order By: Relevance
“…Here, we investigated organic BHJ solar cells containing blends of either MDMO-PPV:PC 61 BM or P3HT:PC 61 BM by temperature dependent TDCF measurements. We observed a strongly field dependent polaron pair dissociation in blends of MDMO-PPV:PC 61 BM, which is in good agreement with its CT exciton binding energy of up to 200 meV, determined by photoluminescence measurements [13,14]. In contrast, an ala Electronic address: deibel@physik.uni-wuerzburg.de most field and temperature independent charge collection was experimentally found in P3HT:PC 61 BM.…”
supporting
confidence: 85%
“…Here, we investigated organic BHJ solar cells containing blends of either MDMO-PPV:PC 61 BM or P3HT:PC 61 BM by temperature dependent TDCF measurements. We observed a strongly field dependent polaron pair dissociation in blends of MDMO-PPV:PC 61 BM, which is in good agreement with its CT exciton binding energy of up to 200 meV, determined by photoluminescence measurements [13,14]. In contrast, an ala Electronic address: deibel@physik.uni-wuerzburg.de most field and temperature independent charge collection was experimentally found in P3HT:PC 61 BM.…”
supporting
confidence: 85%
“…Such CT emission bands have been detected previously for several polymer:fullerene systems, using PL and electroluminescence measurements. 9,10,[43][44][45] The polarization anisotropy r PL (E) spectra for films aligned at 80 • C (Fig. 2) and 110 • C are shown in Fig.…”
Section: A Photoluminescence Anisotropymentioning
confidence: 99%
“…[41] Besides the above mentioned two-step charge generation process, constituted of an excitation of the donor material followed by a charge transfer to the acceptor or vice versa, lately a single step charge generation process via direct excitation of the CT-state located at the donor-acceptor interface has been discovered and discussed with growing intensity. [42][43][44][45][46][47] Early studies using highly sensitive external quantum efficiency measurements already revealed that below both the electronic transitions of neat donor and acceptor in the blend an additional very weak transition exists, representing the CT. [42][43][44][45][46][48][49][50][51][52][53][54] Furthermore it has been shown by electroluminescence (EL) measurements that also the opposite process, i.e., luminescent recombination via a CT-state, can be detected. [42][43][44][45]54,55] One major conclusion was that the transition energy of this CTstate is inherently linked to the energetic separation of charge carriers and thus to the open-circuit voltage of organic solar cells.…”
Section: Introductionmentioning
confidence: 99%